DETERMINASI KUALITAS PENGELOLAAN FASILITAS DAN INFRASTRUKTUR DALAM MENINGKATKAN PEMBELAJARAN DI SEKOLAH DASAR - Nazwa Ramadhani; Salsyabila Is Inaya; Zahrotun Nisa; Suherli Kusmana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the effect of the quality of facilities and infrastructure management on improving learning performance in elementary schools. Educational facilities and infrastructure play an essential role in supporting effective and meaningful learning processes. However, many schools still face limitations in management, utilization, and maintenance of learning facilities. This research used a quantitative approach with a survey method. The subjects of the study were elementary school teachers selected using purposive sampling. Data were collected through questionnaires, observations, and documentation, then analyzed using descriptive and inferential statistics. The results showed that the quality of facilities and infrastructure management has a significant positive effect on learning performance. Schools with well-planned, organized, and maintained facilities tend to have more effective learning processes, higher student engagement, and better learning outcomes. These findings indicate that improving management systems, supervision, and maintenance of educational facilities is an important strategy to enhance the quality of learning in elementary schools. Keywords: facility and infrastructure management, learning performance, elementary school, learning quality